PERSEPSI DAN PENGELOLAAN HOMESTAY DI DESA WISATA WUKIRSARI, BANTUL - Devi Puspitasari; Heddy Shri Ahimsa-Putra; Djoko Wijono (Jurnal Kawistara, 2019)
Homestay is one of criteria for the existence of tourism village. Its existence as one of tourism accommodation forms is important to tourism development in tourism village. Homestay is one of tourism industry where tourist meet the local people. The Government of Indonesia also create a policy for the development of amenities (homestay). Therefore, the perception on homestay concept becomes important for homestay owner. After knowing its concept, the owner can manage their homestay based on homestay management guideline. Homestay management aspects in this research are physic and environment management, human resources, institution and data management, also promotion management. A professional management for the homestay can be the opportunity for local people to make the tourist stay longer and enjoy the natural view as well as the culture in tourism village. The aim of this research is to determine the perceptions of homestay and its management at Wukirsari Tourism Village. The benefit of this research is to provide more references regarding to tourism studies, especially on homestay management. The methods used in this study are observation, interview, and documentation. The result reveals that homestay’s owners at Wukirsari Tourism Village know the concept of homestay, but they lack of knowledge on the management. The writer’s suggestion is training about homestay and its management is needed for homestay owner in Wukirsari tourism village.